Afetividade nas relações entre orientadores e orientandos de cursos de pós-graduação stricto sensu em ciências contábeis - Edleuza Paulina Loures da Silva (2020)
The present study aimed to investigate the perceptions of stricto sensu graduate students in Accounting sciences about the role of affectivity in the students and supervisors’ interaction. The concept of affectivity was based on Jean Piaget, Levi Vygotsky and Henri Wallon’ theories. These authors have devoted much of their research to the study of the individual's intellectual development. Despite presenting different methodologies, their theories are convergent in establishing that the individual develops through interpersonal relationships, and that these are permeated by affectivity. The sample of this study was composed of 309 stricto sensu graduate students in the accounting area, with 65% corresponding to academic master's students, 31.72% academic doctoral students and 2.91% master students professional. The students' perceptions about the orientation relationship were captured through the Questionnaire on Supervisor–doctoral Student Interaction (QSDI) adapted by Mainhard, Rijst, Tartwijk and Wubbel (2009) and the affectivity through the Positive and Negative Affect (Panas) developed by Watson, Clark and Tellegan (1985). Cronbach's Alpha for QSDI was 0.9424 and for Panas 0.9025, attesting the high internal reliability of the scales. The QSDI Exploratory Factor Analysis (EFA) generated a total of six factors (F1: Leadership and friendship, F2: Scolding and dissatisfaction, F3: Understanding. F4: Freedom, F5: Uncertainty and F6: Requirement), which explained 65.53% of the total data’s variability. Panas' EFA generated two factors, for positive and negative affects, which explained 71.47% of the total data’s variability. Multiple Linear Regression Models (MLRM) were built from the factors retained in the EFA of the QSDI. Each factor represented a dependent variable and, therefore, six regressions were estimated. The results showed that the increase in positive affects in the orientation relationship contributes to the increase in leadership, friendship and understanding on the part of the supervisor, in the perception of the students. On the other hand, even in the perception of graduate students, the increase in negative affects favors behaviors aimed at rebuke, dissatisfaction and demand, in addition to contributing to the reduction of understanding and autonomy in the orientation process. It was also observed that the supervisor's understanding tends to be greater when the student is preparing to defend the dissertation or thesis, and that the student linked to a public university has greater freedom in the process of work development compared to students from private universities. Finally, it was found that the requirement on the part of the supervisor tends to be less when the student belongs to the master's degree, has experience in scientific research and is preparing for the defense. Thus, when analyzing the orientation relationship from the point of view of the student, it is concluded that most of the students participating in this study have an affective positive relationship with the supervisor, with aspects such as friendship, understanding, admiration, respect, enthusiasm, among others. However, it was observed that some students presented affectively negative perceptions about the orientation relationship, showing feelings such as fear, stress, lack of interest, frustration, among others, and generating concern about the way some supervisors are conducting their orientations. It is also concluded that, when thinking and dealing with the orientation relationship, they prioritized aspects related to the figure of the supervisor as a person and did not elaborate on the characteristics of the process of orientation and work development. This finding reiterates that students choose and analyze their supervisors adopting the personality traits as the most relevant criteria at the expense of technical training. In the end, this research aims to contribute to the academy by improving scientific research on affectivity in the educational environment. It also contributes to raise reflections for graduate programs on the need to give greater dedication to teacher training, and provides insights so that supervisors and supervisee an reflect on behaviors that should be highlighted or avoided in the process of orientation theses and dissertations.